Evaluation of phenols and limonoids in leaves of Cedrela odorata (Meliaceae) from an experimental plantation established in Tezonapa Veracruz, Mexico - Mariscal-Lucero, Samantha del Rocío (2015)
Cedrela odorata (Meliaceae) is a native timber tree to Tropical America, known for its high-quality wood, unfortunately, plantations of this species are severely attacked by Hypsipyla grandella. The attraction or repellency of this pest is related to secondary metabolites such as phenols and limonoids (triterpenes); therefore, it is important to study these compounds to understand the phytochemical phenomena behind this problem.  With this aim, the concentration of total phenols and limonoides was evaluated in C. odorata leaves from a plantation established in Tezonapa Veracruz, Mexico. For this, a total of 66 tree leaves samples, from seven sites, were analyzed. Phenols and limonoids concentration showed significant differences not only among different provenances, but also among individual trees of the same site (Tukey, p≤0.05). Phenols concentration was variable and in the range from 49 to 223mg EAG/g e for total phenols, from 7 to 158mg EC/g e for flavonoids and from 4 to 104mg EC/g e for proanthocyanidins. Limonoids concentration was also variable, ranging between 227 and 748mg EL/g e. A major compound was found by High-Performance Liquid Chromatography with Ultraviolet Diode Array Detection (HPLC-UV-DAD), which corresponded to a flavonol kaempferol glycoside derivative; additionally, a flavanol catechin was also detected at low concentrations. GC–MS allowed the identification of the sesquiterpenoids β-elemene, E-caryophyllene, aromadendrene, α-humulene, γ-cadinene, D-germacrene, bicyclogermacrene, and the poly terpenoids D-α-tocopherol and β-sitosterol. Our results suggest that the evaluation of phenols may play an important role as a selection parameter for improvement and conservation programs, if they are complemented with conventional breeding practices.